Beginnings - Monk, Meredith 1942- (Sunny Moon, 2009)
Neues Album der Avantgarde-Künstlerin Meredith Monk. Die in Musikerkreisen verehrte, in Peru geborene Amerikanerin ist als Sängerin, Komponistin, Choreografin und Performance-Künstlerin seit den 1960er-Jahren aktiv. Für das aktuelle Album hat sie unveröffentlichte Stücke aus mehreren Jahrzehnten zusammengetragen. Musikalisch spannt sich der Bogen vom Traditional bis zu improvisierten Sound- und Stimm-Collagen. "Fascinating early work from one of the most innovative and far reaching talents of the past several decades - selected by Meredith Monk herself from her personal archives! Beginnings features material that stretches back to the mid 60s, and more from the 70s & early 80s" (www.dustygroove.com).
Enth.: Greensleeves. Nota. Duet for voice and echoplex. Candy bullets and moon. Trance. Epic I. Paris. Biography. Mill. The tale. Quarry weave. Epic II. Tower. Mill. Do you be? Quarry procession. Porch